Immune responses to AAV vectors, from bench to bedside - Hildegard Buning (Frontiers Research Topics, 2015)
The recent wave of clinical studies demonstrating long-term therapeutic efficacy highlights the enormous potential of gene therapy as an approach to the treatment of inherited disorders and cancer. While in recent years lentiviral vectors have dominated the field of ex vivo gene therapy in man, adeno-associated virus (AAV) vectors have become the platform of choice for the in vivo gene delivery, both local and systemic.Despite the achievements in the clinic however, a number of hurdles remain to be overcome in gene therapy, these include availability of scalable vector production systems, potential issues associated with insertional mutagenesis, and concerns related to immunogenicity of gene therapeutics. For AAV vectors, clinical trials showed that immunity directed against the vector could either prevent transduction of a target tissue or limit the duration of therapeutic efficacy. Initial observations in the context of a gene therapy trial for hemophilia spurred over a decade efforts by gene therapists and immunologists to understand the mechanism and identify factors that contribute to AAV's immunogenicity, including the prevalence of B cell and T cell immunity to wild type AAV in humans and the interaction of AAV vectors with the innate and adaptive immune system. Despite a number of important contributions in particular in the more recent past, our knowledge on the immunology of gene transfer is still rudimental; this is partly due to the fact that the basic understanding of the complex balance between tolerance and immunity to an antigen, key aspect of gene transfer with AAV, keeps evolving rapidly. However, continuing work towards a better definition of the interaction of viral vectors with the immune system has led to significant advances in the knowledge of the factors influencing the outcome of gene transfer, such as the vector dose, the immune privilege of certain tissues, and the induction of tolerance to an antigen. A better understanding of the structure-function relationship of the viral capsid has boosted the development of novel immune-escape vector variants. In addition, novel immunomodulatory strategies were established to prevent or reduce anti-capsid immunity have been developed and are being tested in preclinical models and in clinical trials. Together, these advances are bringing us closer to the goal of achieving safe and sustained therapeutic gene transfer in humans. In this research topic, a collection of Original Research and Review Articles highlights critical aspects of the interaction between gene AAV vectors and the immune system, discussing how these interactions can be either detrimental or constitute an advantage, depending on the context of gene transfer, and providing tools and resources to better understand the issue of immunogenicity of AAV vectors in gene transfer.